LA GESTIÓN DEL ACCOUNTABILITY, EL CASO DE ANTIOQUIA - Agudelo Henao, Luis Fernando (Cuadernos de Administración, 2006)
The public management has, within the essential challenges for its development, the construction of identification methodologies and valuation of the social relations. Social accountability, understood as possibility of effective surrender of accounts on the part of the public agents, is constituted in an essential function of the task of the State. In this measurement, the public management has in accountability a novel social relation in our context which is waiting to be identified and to be quantified as a factor of construction of participatory democracy and fortification of the representative democracy. The work analyses the typical structure of the financial and social information systems of the municipalities of Antioquia and it characterizes them based on its size and indicators of the resources management. In equal way it establishes a series of minimum directions to manage the participation and the transparency, starting from the possibility of the consolidation of the territory, and of the political will of the public local leaders to give greater power to the social organizations and also to associate and solve the problems beyond the municipality field.